Analisis Tingkat Pendidikan Terhadap Penempatan Jabatan pada Biro SDM Polda Lampung - Ariyanto Ariyanto; Oktaviannur Oktaviannur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of education level on job placement within the Human Resources Bureau of Lampung Regional Police (Biro SDM Polda Lampung). Appropriate job placement is a crucial aspect of human resource management in supporting organizational effectiveness and performance within the police institution. However, in practice, there are still indications of mismatches between personnel education levels and the positions they occupy. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with informants directly involved in personnel planning and placement at the Human Resources Bureau of Lampung Regional Police, supported by documentation review of relevant regulations and policies. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that education level plays an important role in job placement; however, it has not yet become the primary consideration in placement practices. Job placement is still influenced by organizational needs and pragmatic considerations, resulting in mismatches between educational qualifications and certain positions. Normatively, placement policies have referred to the merit system principle as stipulated in Police regulations, although its implementation in practice still requires further strengthening. This study concludes that optimizing job placement based on education level and competence needs to be enhanced through stronger implementation of the merit system, in order to achieve more effective, fair, and performance-oriented personnel management within the police organization.